Computer games : 6th Workshop, CGW 2017, held in conjunction with the 26th International Conference on Artificial Intelligence, IJCAI 2017, Melbourne, VIC, Australia, August, 20, 2017, Revised selected papers /: 6th Workshop, CGW 2017, held in conjunction with the 26th International Conference on Artificial Intelligence, IJCAI 2017, Melbourne, VIC, Australia, August, 20, 2017, Revised selected papers. (2018) - Unknown
No abstract available